Saturação por bases e híbridos de milho sob sistema plantio direto - Prado, Renato De Mello [UNESP] (2001)
The knowledge of the hybrids of suitable maize to each condicion of the ground in under no-tillage is of significant importance technique. To evaluate the response of corn hybrids to base saturation levels (V%), two experiments were performed with V% equal to 45 and 65, in cerrado areas of Uberaba, MG, Brazil, four years under no-tillage. A completely randomized block design was used, with four replications. Seven corn hybrids represent the treatments: Z 8474, BR3123, AG 122, C 333, D 657, Exceller and P 3071. The results showed that the base saturation of 65% contributed more for the increments in yield components and for the grain yield than the 45% base saturation level. The hybrids presented different yield responses, the highest beeing for the 65% base saturation treatment: P 3071 and Z 8474 and 2); for the 45% base saturation treatment: C 333. Choosing the right hybrids for each base saturation level is an important criterium to maximize corn yields under no-tillage in the cerrado region of Brazil.